Determination of optimum concentration of lime solution for soil stabilization - Ng, Pui Ling (2005)
The main objective of this research is to determine the optimum concentration of lime solution for soil stabilization. Dry lime, either quicklime or hydrated lime is being use currently as soil stabilization agent. Although it is very useful in soil stabilization, it always causes dusting problem and is corrosive to human skin. To avoid these problems, application of lime in solution form is suggested in this research. Several soil tests had been carried out on the untreated soil and lime before the lime added to soil for stabilization to ensure the soil is suitable to be stabilized by lime. After those soil properties determined, the lime solution with different concentration will be added to the soil samples for stabilization for 0, 7, 14 and 28 days. The unconfined strength test is carried out on cured soil to evaluate the effectiveness of lime stabilization with different concentration of the lime solution. The concentration of the lime solution that gives the highest soil strength is the optimum concentration of lime solution for soil stabilization. From the result in this research, the highest Unconfined Compressive Strength achieved is 730 kPa, by stabilized the kaolin with 1.35M lime solution and cured for 28 days. Consequently, this value is the optimum concentration of lime solution for soil stabilization.